A review on frontiers in plasmonic nano-photocatalysts for hydrogen production. (23rd April 2019) - Reddy, N. Lakshmana; Rao, V. Navakoteswara; Vijayakumar, M.; Santhosh, R.; Anandan, S.; Karthik, M.; Shankar, M.V.; Reddy, Kakarla Raghava; Shetti, Nagaraj P.; Nadagouda, M.N.; Aminabhavi, Tejraj M.
Abstract: Nanoparticles have plenty of active sites in each particle and short travel distance for photoexcitons proved to be beneficial characteristics for photocatalytic hydrogen generation. Noble metal (Au, Ag, Pt, Pd, Ru, and Rh) attached with semiconductor photocatalyst displayed plasmonic oscillations results in localized surface plasmon resonance (LSPR) effect and schottky junction formed to pump the photoelectrons to surface for reactions. Literature reports evidenced that the choice of synthesis method and experimental conditions directly affects the catalytic and optical properties. Hence, this review discusses comprehensive information on chemical methods reported for the preparation of plasmonic photocatalyst that resulted in co-catalyst and visible light sensitizer properties. Recent developments and achievements on plasmonic photocatalyst for hydrogen production in pure water and sacrificial agent containing water are discussed and highlighted. Highlights: Effective control of charge carrier injection and extraction on metal oxide photocatalysts. Preparative methods for synthesis of noble metal and metal oxide-based nanocomposites. Photocatalysts design concepts using noble metal as co-catalyst and visible light sensitizer. Size effects of noble metal on two types of interaction between metal and metal oxides. Present status and future directions on photocatalytic hydrogen production.